Poultry processing and value addition in Bangladesh- A review - Hashem, MA; Sarker, MSK; Nurul Alam, AMM; Mia, N; Rahman, MM (Meat Research, 2024)
The poultry sector in Bangladesh has experienced substantial expansion, establishing itself as a crucial element of the country's agricultural economy. Bangladesh is experiencing significant growth in its commercial poultry industry, which includes the commercial processing of chicken. The increase in poultry processing factories is driven by the notion that this particular industry offers better food and presents lower risks of food-borne diseases compared to traditional processing in wet markets. This review examines the various complex aspects of chicken processing and further processing along with product dimensions in Bangladesh market. Furthermore, it presents a thorough analysis of the poultry processing industry in Bangladesh and provides valuable insights on how to optimize its ability to add value, to fulfill the demands of both the domestic and export markets.